Motivation of Farmers in The Corporate Farming Program in Gapoktan Sidomulyo Kapanewon Godean Sleman Regency - Fitri Laela Rahmawati; Alia Bihrajihant Raya; Harsoyo Harsoyo; Diah Fitria Widhiningsih (Agro Ekonomi, 2022)
Corporate Farming is a program that establishes farmer economic institutions with legal entities in the form of cooperatives or others to encourage the empowerment of agricultural institutions in overcoming farming problems. With the new program issued by the government, hopefully, farmers have the motivation to participate and implement the program to improve the welfare of farming businesses. The aims of this study are: 1) to portray the level of motivation of farmers in participating in the corporate farming program at the Sidomulyo Farmers Association (Gapoktan) in Sidomulyo Urban Village, Kapanewon Godean, Sleman Regency; 2) to comprehend the factors that influence the motivation of farmers in participating in the corporate farming program at the Sidomulyo Farmers' Association in Sidomulyo Urban Village Kapanewon Godean, Sleman Regency. The research applies a descriptive method with a quantitative approach. The combined sampling of farmer groups is carried out by purposive sampling, namely the Sidomulyo Farmer Group Association. Furthermore, the research respondents are selected by simple random sampling on all members of the Farmer Group Association who participated in the corporate farming program. So, the total respondents are 40 farmers. The analysis in this study uses the proportion test and multiple linear regression. The results show that most farmers (more than 50%) in Gapoktan Sidomulyo have a high level of motivation to take part in the program. The factors that significantly influence the motivation of farmers to participate in the corporate farming program are the role of Gapoktan and the accomplishment of the corporate farming program. The factors that have no significant impact on the motivation of farmers to participate in the program are the level of education, land area, farm income, and the number of dependents of the family.